Neopterin, kynurenine and tryptophan as new biomarkers for early detection of rectal anastomotic leakage - Dusek, Tomas; Orhalmi, Julius; Sotona, Otakar; Krcmova, Lenka Kujovska; Javorska, Lenka; Dolejs, Josef; Paral, Jiri (Wideochirurgia i inne techniki maloinwazyjne, 2018)
INTRODUCTION: At present, there are no strong predictors, nor a useful scoring system, that clearly identifies patients at risk for anastomotic leakage. AIM: This study aimed to investigate a new method that assesses this risk by monitoring levels of neopterin, tryptophan, and kynurenine, in bodily fluids. MATERIAL AND METHODS: This prospective study included patients who underwent elective rectal resection for carcinoma. The basic condition for inclusion was rectal anastomosis using the double-stapling technique. Preoperative levels of neopterin, tryptophan, kynurenine, and their ratios, were assessed with blood and urine samples. These levels were then monitored for 6 postoperative days in venous blood, urine, and abdominal drainage fluid. RESULTS: A total of 42 patients were enrolled in the study. Thirty-six patients underwent a laparoscopic resection and 6 patients had an open procedure. No differences were found among neopterin, tryptophan, and kynurenine serum levels. However, the groups were observed to have significant differences in the urinary neopterin/creatinine ratio: the preoperative neopterin/creatinine ratio was 139.5 μmol/mol in the group with leakage, vs 114.8 μmol/mol in the group without complications, p = 0.037. The same results were observed during the postoperative period, p = 0.012. Additionally, the group with complications had a higher mean value of neopterin in drainage fluid, p = 0.048. CONCLUSIONS: Our study demonstrated that high preoperative levels of urinary neopterin could be interpreted as a risk for anastomotic leakage. Moreover, pathological levels of neopterin in urine and abdominal drainage fluid could be useful for early identification of anastomotic leakage during the postoperative period prior to its clinical development.
Keywords: anastomotic leak; kynurenine; neopterin; rectal carcinoma; tryptophan